Mapping Platform Urbanism: Charting the Nuance of the Platform Pivot - Lee, Ashlin (2020)
Urban planners are increasingly working with ideas around datafied cities, such as platform urbanism, to understand urban life and changes with technology. This article seeks to assist urban planners in these efforts by analysing and mapping the qualities of platform urbanism. Drawing on a dataset of approximately 100 examples that detail urban data practices, we trace some of the current tendencies that are shaping the nature and dynamics of platform urbanism. While we identify no unifying narrative or overarching pattern to our data, we interpret this as supporting Barns’ (2019) notion of a pivot towards platforms. We argue this through exploring the interoperability between data sources and domains (vertical and horizontal integration), identifying elements of how platforms intermediate urban life through their growth in different sectors and the use of geolocation, and note the different artefacts that contribute to platform urbanism. We also note a concerning dynamic where city administration becomes ‘locked in’ to specific corporate products and interests, and thereby ‘locked out’ from alternatives. We discuss this in the context of social inclusion and what this means for urban planners, including the fragility of corporate platforms and what platforms urbanism means for social relationships in the city.